An Assessment of the Viability of Lytic Phages and Their Potency against Multidrug Resistant Escherichia coli O177 Strains under Simulated Rumen Fermentation Conditions - Peter Kotsoana Montso; Caven Mguvane Mnisi; Collins Njie Ateba; Victor Mlambo (MDPI AG, 2021)
Preslaughter starvation and subacute ruminal acidosis in cattle are known to promote ruminal proliferation of atypical enteropathogenic Escherichia coli strains, thereby increasing the risk of meat and milk contamination. Using bacteriophages (henceforth called phages) to control these strains in the rumen is a potentially novel strategy. Therefore, this study evaluated the viability of phages and their efficacy in reducing E. coli O177 cells in a simulated ruminal fermentation system. Fourteen phage treatments were allocated to anaerobic serum bottles containing a grass hay substrate, buffered (pH 6.6-6.8) bovine rumen fluid, and E. coli O177 cells. The serum bottles were then incubated at 39 °C for 48 h. Phage titres quadratically increased with incubation time. Phage-induced reduction of E. coli O177 cell counts reached maximum values of 61.02-62.74% and 62.35-66.92% for single phages and phage cocktails, respectively. The highest E. coli O177 cell count reduction occurred in samples treated with vB_EcoM_366B (62.31%), vB_EcoM_3A1 (62.74%), vB_EcoMC3 (66.67%), vB_EcoMC4 (66.92%), and vB_EcoMC6 (66.42%) phages. In conclusion, lytic phages effectively reduced E. coli O177 cells under artificial rumen fermentation conditions, thus could be used as a biocontrol strategy in live cattle to reduce meat and milk contamination in abattoirs and milking parlours, respectively.